Aging With Grace: The Quest for Integrated, Compassionate Care for Older Adults - Anat Romem; Beth G. Zalcman; Emilia Katz; Tal Prager (SAGE Publishing, 2024)
Introduction This Practice Update discusses the potential for implementation of the 4M model for care of older adults in Israel, to complement the medical-centric model that exists today. The older adult population in Israel is increasing. However, efficient and sufficient care that takes patient's wishes into consideration is lacking. Purpose Care of older adults, particularly palliative patients, is complex and requires multidisciplinary efforts. There are numerous challenges to caring for older adults. These include fragmentation of care, unclear boundaries between palliative and geriatric care, and the preservation of patient autonomy, indicating a need to adopt new care frameworks. Conclusion The authors suggest implementing the 4M model as a new care framework in addition to the current medical-centric model. This framework considers important care aspects during discussions of care: what matters to the patient, medication, mentation, and mobility. Implementation of this model can promote better-integrated care, thus improving the quality of life for older adults.